2017
DOI: 10.3390/w9120930
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Effectiveness of Streambank Stabilization Practices on Cedar River, Nebraska

Abstract: Excessive sediment is a major pollutant to surface waters worldwide. In some watersheds, streambanks are a significant source of this sediment, leading to the expenditure of billions of dollars in stabilization projects. Although costly streambank stabilization projects have been implemented worldwide, long-term monitoring to quantify their success is lacking. There is a critical need to document the long-term success of streambank restoration projects. The objectives of this research were to (1) quantify stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…Its streambanks have been stabilized, successfully or unsuccessfully, with various techniques over a period of many decades. Two previous studies conducted on the Cedar River evaluated the effectiveness of streambank stabilization structures on streambank erosion and deposition (Dave and Mittelstet, 2017;Russell et al, 2021). Dave and Mittelstet (2017) quantified the streambank retreat before (0.45 m 2 m -1 year -1 ) and after (0.16 m 2 m -1 year -1 ) the stabilization of 18 streambanks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Its streambanks have been stabilized, successfully or unsuccessfully, with various techniques over a period of many decades. Two previous studies conducted on the Cedar River evaluated the effectiveness of streambank stabilization structures on streambank erosion and deposition (Dave and Mittelstet, 2017;Russell et al, 2021). Dave and Mittelstet (2017) quantified the streambank retreat before (0.45 m 2 m -1 year -1 ) and after (0.16 m 2 m -1 year -1 ) the stabilization of 18 streambanks.…”
mentioning
confidence: 99%
“…Two previous studies conducted on the Cedar River evaluated the effectiveness of streambank stabilization structures on streambank erosion and deposition (Dave and Mittelstet, 2017;Russell et al, 2021). Dave and Mittelstet (2017) quantified the streambank retreat before (0.45 m 2 m -1 year -1 ) and after (0.16 m 2 m -1 year -1 ) the stabilization of 18 streambanks. They found that the stabilized banks were more efficient than the control sites at reducing erosion.…”
mentioning
confidence: 99%
“…From 2000 to 2005, streambank stabilization projects were implemented to reduce streambank erosion and improve surface water quality. Through the Cedar River Stabilization Project, 20 streambanks were stabilized using six different techniques, predominantly wooden log jetties, along the river, of which four were constructed between Ericson Dam and Spalding Dam (Dave and Mittelstet 2017).…”
Section: Site Descriptionmentioning
confidence: 99%
“…The research articles included in this special issue specifically targeted three areas that are key to better understanding streambank erosion and failure, namely, monitoring [8][9][10][11], modeling [12][13][14][15][16][17], and management [18][19][20][21]. As an ensemble, the articles highlight the value of monitoring campaigns to characterize the effect of external drivers (e.g., hydrologic events), the capabilities and limitations of numerical models for predicting the response of the system (e.g., stream restoration design), and the effectiveness of management practices to prevent and mitigate the impacts of streambank erosion and failure.…”
Section: Main Outcomes Of the Special Issuementioning
confidence: 99%
“…Dave and Mittelstet [20] evaluated the effectiveness of six stabilization practices (e.g., jetties, rock vanes) that were implemented across 18 different bank locations. They used aerial imagery to quantify pre-and post-stabilization bank retreat and to assess the impact of a major storm event that took place during the evaluation period.…”
Section: Managementmentioning
confidence: 99%